By the Honorable William Dummer, Esq., Lieut. Governour & Commander in Chief, in & over His Majesty's Province of the Massachusetts-Bay in New-England : a proclamation for apprehending John Pittman ... Given at the Council Chamber in Boston, the twenty-fourth day of February, 1726 . (Printed by B. Green, printer to His Hon. the Lieut. Gov. & Council, 1726)
February 24, 1726 Broadside that is a wanted poster for the capture of a fleeing suspect, John Pittman. The proclamation, issued by Lieut. Gov. William Dummer of Massachusetts Bay, described the underlying criminal circumstances, as well as a general description of the suspect. Reimbursement of cost associated with the capture were also guaranteed.